2022
DOI: 10.2147/cia.s374857
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Muscle Degeneration: A Potential Risk Factor for New Vertebral Compression Fractures After Percutaneous Kyphoplasty

Abstract: Background The paraspinal muscle is essential for maintaining normal spine function and structure, which degeneration is closely related to various spinal diseases. The main objective of this study was to identify the potential role of paraspinal muscle degeneration in the occurrence of new vertebral compression fractures (NVCF) and develop a clinically applicable nomogram for prospective NVCF risk prediction. Methods A total of 202 patients with single-level osteoporot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Hence, we speculate that vertebral attachment to a dysfunctional MFM is less effective against perturbations and thus more susceptible to subsequent vertebral fracture. Consistent with this, previous research reported that incomplete MFM function was associated with bone nonunion after lumbar interbody fusion [ 22 ], new compression fracture after vertebroplasty [ 28 ], and OVCF [ 32 ]. We also found that, although the rFCSA and FI of the MFM at the L3/4 and L4/5 IVD levels were associated with fracture, only rFCSA of the MFM at the L4/5 IVD level was an independent risk factor, even for OVCF at other levels, indicating that this factor best reflects overall MFM function and its influence on subsequent vertebral fracture.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Hence, we speculate that vertebral attachment to a dysfunctional MFM is less effective against perturbations and thus more susceptible to subsequent vertebral fracture. Consistent with this, previous research reported that incomplete MFM function was associated with bone nonunion after lumbar interbody fusion [ 22 ], new compression fracture after vertebroplasty [ 28 ], and OVCF [ 32 ]. We also found that, although the rFCSA and FI of the MFM at the L3/4 and L4/5 IVD levels were associated with fracture, only rFCSA of the MFM at the L4/5 IVD level was an independent risk factor, even for OVCF at other levels, indicating that this factor best reflects overall MFM function and its influence on subsequent vertebral fracture.…”
Section: Discussionsupporting
confidence: 76%
“…An important finding of our study was that rFCSA of the MFM at the L4/5 IVD level was an independent risk factor for subsequent vertebral fracture. Among the paraspinal muscles, the MFM is the strongest stabilizer of the lumbar spine [ 28 ]. The effect of the bilateral MFM accounts for more than two-thirds of the spine stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Si et al ( 59 ) conduced a similar study on patients after percutaneous kyphoplasty and observed that multifidus, psoas, and erector spinae muscles fatty infiltration was correlated with the occurrence of new OVCF after undergoing the procedure. They also observed that the CSA difference index between multifidus muscle and psoas muscle represented a risk factor for the recurrence of OVCF.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Kanis et al [27] identi ed a history of prior fractures as one of the most in uential factors contributing to the occurrence of new fractures in postmenopausal women. Additionally, high-risk factors for NVCF include paraspinal muscle degeneration, bone cement leakage into the intervertebral disc, the initial fracture occurring at the thoracolumbar junction, the natural progression of osteoporosis, and the volume of bone cement injected [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%